Effects of water flow velocity and fish culture on net biofouling in fish cages - Madin, J.; Chong, V.C.; Hartstein, N.D. (Blackwell Publishing, 2010)
The effects of water flow, fish feed and cage position on net biofouling was examined in a floating cage fish farm. Fouling of 16 mm mesh net panels suspended inside and outside net cages and exposed to different treatments were monitored weekly until net apertures were completely occluded by the fouling organisms (8 weeks). Results indicate a dramatic reduction in water flow velocity throughout the fish farm due to the cage units themselves and net biofouling. The reduced water flow (< 10 cm s-1) inside net cages promoted rapid net biofouling, while rapid water flow outside the net cages (> 25 cm s-1) kept the net fouling organisms at bay. Although fish rearing in net cages with inputs of commercial pellet feed increased sessile biofouling (222% higher than outside the net cages) and non-sessile biofouling (570% higher), the type of fish feed used did not significantly affect biofouling development. The study recommends that the geometry of serially arranged net cages, as commonly deployed in tropical tidal estuaries, be reconfigured to improve flow through in order to minimize the impact of fouling.